Pengaruh Media Sosial terhadap Pola Kejahatan di Era Digital: Studi Kriminologi dengan Pendekatan Netnografi - Hukom, Rafli; Setiadi, Martinus Hukmu (Perkara : Jurnal Ilmu Hukum dan Politik, 2025)
The rapid development of social media has transformed digital crime patterns, enabling financial fraud, exploitation, and radicalization to spread more efficiently. In Indonesia, cybercrime cases have increased by 60% over the past five years, yet law enforcement remains ineffective due to the complexity of digital crime and limited regulatory enforcement. This study aims to analyze how social media facilitates cybercrime, the evolving modus operandi of criminals, and the effectiveness of existing legal frameworks. This research employs a netnographic approach, combining qualitative content analysis of online interactions with secondary data from law enforcement reports. Findings indicate that digital fraud cases have risen by 85% in the past three years, with cryptocurrency-related scams causing losses of IDR 5.2 trillion. Cyberbullying and defamation cases have surged by 60% since 2018, while only 22% of reported cybercrimes have been legally processed, with a conviction rate of just 6%. These figures highlight significant gaps in digital forensic capabilities and cross-sector collaboration. This study contributes to understanding the role of social media in shaping cybercrime and provides policy recommendations to enhance crime prevention strategies. Strengthening legal frameworks, improving law enforcement technology, and fostering cooperation between stakeholders are essential to addressing cybercrime in the digital era. Future research should focus on comparative legal studies and the role of artificial intelligence in cybercrime detection